Pengaruh Efikasi Diri, Motivasi Memasuki Dunia Kerja, Dan Keaktifan Berorganisasi Terhadap Kesiapan Kerja Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Dharma Andalas - Repi Anggraini; Rita Srihasnita RC (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine the effect of Self-Efficacy, Motivation to Enter the World of Work, and Organizational Activity on the Work Readiness of Students of the Faculty of Economics and Business, Dharma Andalas University. The population in this study were 225 students at the Faculty of Economics and Business. The sample in this study was 144 people with the criteria of students who have work readiness. This study is included in quantitative research. The instrument used in this study was a questionnaire. The results of the study using multiple linear regression analysis showed that simultaneously there was a significant influence between self-efficacy, motivation to enter the world of work, and organizational activity on student work readiness and partially self-efficacy had a positive and significant effect on student work readiness, partially motivation to enter the world of work had a positive and significant effect on student work readiness, partially organizational activity had a positive and significant effect on student work readiness.